Protein Databases Related to Liquid–Liquid Phase Separation - Li, Qian (Int J Mol Sci, 2020)
Liquid−liquid phase separation (LLPS) of biomolecules, which underlies the formation of membraneless organelles (MLOs) or biomolecular condensates, has been investigated intensively in recent years. It contributes to the regulation of various physiological processes and related disease development. A rapidly increasing number of studies have recently focused on the biological functions, driving, and regulating mechanisms of LLPS in cells. Based on the mounting data generated in the investigations, six databases (LLPSDB, PhaSePro, PhaSepDB, DrLLPS, RNAgranuleDB, HUMAN CELL MAP) have been developed, which are designed directly based on LLPS studies or the component identification of MLOs. These resources are invaluable for a deeper understanding of the cellular function of biomolecular phase separation, as well as the development of phase-separating protein prediction and design. In this review, we compare the data contents, annotations, and organization of these databases, highlight their unique features, overlaps, and fundamental differences, and discuss their suitable applications.